Preparation method and application of chitosan derivative carbon electrode

CN120398202BActive Publication Date: 2026-10-30NANJING TECH UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510378492.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2026-10-30
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

但传统碳材料的电化学吸附沉积能力一般,比如论文“秸秆生物炭电极用于直流电化学法去除水中重金属(doi.org/10.1016/j.jclepro.2022.130746)”中,虽然秸秆生物炭材料成本低廉,但去除率仅达76.6%;而一些报道中,则使用碳纳米管、氧化石墨烯制备电极,虽然普遍取得良好效果,但此类材料价格十分昂贵

Benefits of technology

[0025](1)本发明中CS作为碳源碳化能形成孔隙多、比表面积大、化学结合位点多的碳材料,多孔隙、大比表面积能使之有效接触活化剂,也能为后续氮化杂化提供大量空位;精氨酸作为氮源,在热分解时释放大量甲胺、NH3、氰酸等小分子氮进入碳材料孔隙中进行反应,氮于其中有效地晶格化,形成吡啶氮、氨基氮、吡咯氮、氮氧化物等,从而改变原子电子结构、增加其导电性、形成sp2杂化C的离域共轭体系,进而导致材料的电催化性能显著改变;再者精氨酸、IAA高温热分解时产生的气体,如CO2、NH3有利于促进形成孔结构、提高比表面积,利于物质扩散传递反应产生更多的催化活性位点;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120398202B_ABST
    Figure CN120398202B_ABST
Patent Text Reader

Abstract

The application discloses a kind of chitosan derivative carbon electrode and preparation method and application, belong to environmental protection material field, steps are as follows: carbon felt is activated by hot soaking in nitric acid-hydrochloric acid mixed acid, and modified carbon felt carrier is prepared;CS, arginine, indole-3-acetic acid (IAA) are dissolved in water, and CS-arginine-IAA precursor solution is obtained, then precursor solution is placed in hydrothermal reaction kettle with carbon felt at low temperature hydrothermal carbonization, and CS hydrothermal carbonization carbon felt is obtained;Potassium hydroxide, potassium silicate are dissolved in water, and activation strengthening liquid is prepared, and activation strengthening liquid is loaded to CS hydrothermal carbonization carbon felt;After CS hydrothermal carbonization carbon felt containing activation strengthening liquid is activated by high temperature pyrolysis, after washing with dilute hydrochloric acid, deionized water is washed, and dried, finally, CS derivative carbon electrode is obtained;The CS derivative carbon electrode prepared by the application has good electrochemical performance, good heavy metal ion electrodeposition removal performance, and can efficiently electrochemically deposit and remove heavy metal ions in wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmental protection and water treatment, specifically to a method for preparing and applying a chitosan CS-derived carbon electrode. Background Technology

[0002] Heavy metal pollution in water is mainly caused by mining, industrial wastewater discharge, and irrigation using wastewater containing heavy metals. Excessive heavy metals in the environment not only harm the ecological environment but also seriously damage human health through direct contact and bioaccumulation in the food chain. Conventional methods for removing heavy metal ions include chemical precipitation, adsorbent adsorption, and membrane separation; however, these methods generally suffer from low efficiency, high cost, or the potential for secondary pollution. Electrochemical removal technology for heavy metal ions has attracted widespread attention due to its simplicity, lack of secondary pollution, and ability to efficiently recover heavy metals in their metallic state. The performance of the electrode materials directly affects the effectiveness of electrochemical removal.

[0003] Carbon materials are ideal electrode materials due to their good conductivity, high stability, and strong adsorption capacity. However, the electrochemical adsorption and deposition capabilities of traditional carbon materials are generally limited. For example, in the paper "Straw biochar electrode for the removal of heavy metals from water by DC electrochemical method (doi.org / 10.1016 / j.jclepro.2022.130746)," although straw biochar material is inexpensive, the removal rate only reached 76.6%. In some reports, carbon nanotubes and graphene oxide have been used to prepare electrodes, which generally achieve good results, but these materials are very expensive. Summary of the Invention

[0004] The purpose of this invention is to propose a method for preparing a CS-derived carbon electrode and to apply it to the electrochemical deposition of heavy metal ions in water.

[0005] This invention uses CS as a carbon source, arginine as a nitrogen source, indole-3-acetic acid (IAA) as a hybridization promoter, potassium hydroxide as an activator, and potassium silicate as an activation enhancer to prepare a CS-derived carbon electrode by low-temperature hydrothermal combined with high-temperature pyrolysis. This electrode can electrochemically deposit heavy metal ions into a metallic state on the electrode, allowing the heavy metals to be recycled in a metallic state. It has good performance in removing and recycling heavy metals and is a new type of high-efficiency and environmentally friendly electrode material.

[0006] The specific technical solution of this invention is as follows:

[0007] A method for preparing a CS-derived carbon electrode, comprising the following steps:

[0008] (1) Pretreatment of carbon fiber felt: The carbon fiber felt is immersed in a mixture of nitric acid and hydrochloric acid and heated, then taken out, washed with deionized water, and dried to obtain modified carbon felt carrier.

[0009] (2) Preparation and loading of CS, arginine, and indole-3-acetic acid IAA precursor solution onto modified carbon felt: Chitosan CS, arginine, IAA, and glacial acetic acid were dissolved in deionized water and stirred to prepare CS-arginine-IAA precursor solution.

[0010] (3) Low-temperature hydrothermal carbonization: The modified carbon felt carrier is immersed in the CS-arginine-IAA precursor solution prepared in step (2) and subjected to hydrothermal carbonization reaction. After hydrothermal carbonization, it is taken out and dried, which is called CS hydrothermal carbonization electrode.

[0011] (4) Preparation and loading of activation and strengthening agent onto CS hydrothermal carbonization electrode: Dissolve potassium hydroxide and potassium silicate in deionized water to prepare activation and strengthening solution; immerse CS hydrothermal carbonization electrode in activation and strengthening solution and stir to wet it; take out CS hydrothermal carbonization electrode containing activation and strengthening solution and dry it to obtain CS hydrothermal carbonization electrode containing activation and strengthening agent.

[0012] (5) High-temperature pyrolysis activation: The hydrothermal carbonization electrode containing activator CS prepared in step (4) is placed in a tube furnace, pyrolyzed at high temperature with inert gas as protective gas, and taken out after cooling. The product is called CS high-temperature pyrolysis electrode.

[0013] (6) Post-processing: The CS high-temperature pyrolysis electrode prepared in step (5) is immersed in dilute hydrochloric acid, washed with deionized water, and dried in an oven to finally obtain the CS-derived carbon electrode.

[0014] In the technical solution of the present invention: in step (1), the mass ratio of nitric acid, hydrochloric acid and water in the nitric acid-hydrochloric acid mixed acid is 1:(1~4):10, the heating temperature is 50~70℃, the drying temperature is 50~80℃, and the drying time is 2~4h.

[0015] In the technical solution of this invention: in step (2), the mass ratio of CS, arginine, IAA, glacial acetic acid and deionized water in the CS-arginine-IAA precursor solution is (2-4):(1-2):(0.5-1):2:100.

[0016] In the technical solution of the present invention: in step (3), the hydrothermal carbonization temperature is 200-240℃, the hydrothermal carbonization time is 10-12h, the drying temperature is 50-80℃, and the drying time is 2-4h.

[0017] In the technical solution of this invention: in step (4), the mass ratio of potassium hydroxide, potassium silicate and deionized water in the activation and strengthening liquid is (1~2):(0.5~1):100; the drying temperature is 50~80℃ and the drying time is 2~4h.

[0018] In the technical solution of this invention: in step (5), the inert gas is nitrogen, the heating rate is 3-5℃ / min; the high-temperature pyrolysis temperature is 900-1000℃, the holding time is 0.5-1h; and the cooling rate is 3-5℃ / min.

[0019] In the technical solution of the present invention: in step (6), the concentration of dilute hydrochloric acid is 0.05-0.1 mol / L, the soaking time is 4-6 h, the drying temperature is 50-80℃, and the drying time is 2-4 h.

[0020] A chitosan-derived carbon electrode, which is prepared by the above method.

[0021] The electrodes prepared by the above method are used in the electrochemical deposition method for removing heavy metal ions from water.

[0022] Experimental conditions and results of this invention:

[0023] Experiments were conducted to remove heavy metal ions using simulated wastewater. The main component of the simulated wastewater containing copper ions was CuSO4. 2 + The concentration was 300 ppm, and the supporting electrolyte was Na2SO4 with a concentration of 400 ppm; the main components of the lead ion simulated wastewater were Pb(NO3)2 and Pb. 2+ The concentration was 200 ppm, and the supporting electrolyte was NaNO3 with a concentration of 400 ppm. A pulsed potential of -1 to -6 V (relative to the reference electrode), a duty cycle of 75%, and a frequency of 100 Hz were applied to the CS-derived carbon electrode. Experimental results showed that, after 1.5 h, Cu... 2+ Pb 2+ The removal rates all exceeded 70%, and Cu was removed after 3 hours. 2+ Pb 2+ The removal rates all exceeded 90%, and a large amount of deposits were observed on the electrodes after the experiment.

[0024] The beneficial effects of this invention are as follows:

[0025] (1) In this invention, CS is used as a carbon source to form carbon materials with many pores, large specific surface area, and many chemical bonding sites. The high porosity and large specific surface area enable effective contact with activators and provide a large number of vacancies for subsequent nitridation and hybridization. Arginine is used as a nitrogen source. During thermal decomposition, it releases a large amount of small molecule nitrogen such as methylamine, NH3, and cyanic acid into the pores of the carbon material to react. The nitrogen is effectively crystallized in the pores to form pyridine nitrogen, amino nitrogen, pyrrole nitrogen, nitrogen oxides, etc., thereby changing the atomic electronic structure, increasing its conductivity, and forming sp 2The delocalized conjugated system of hybrid C leads to a significant change in the electrocatalytic performance of the material; furthermore, the gases produced during the high-temperature thermal decomposition of arginine and IAA, such as CO2 and NH3, are conducive to the formation of porous structures, increase the specific surface area, and facilitate the diffusion and transfer of matter to generate more catalytic active sites.

[0026] (2) In this invention, IAA is a hybridization promoter. The IAA molecule contains both carboxyl and indole rings. The carboxyl group can form hydrogen bonds with the hydroxyl or amino groups of chitosan and form a gel structure network when dissolved. The indole ring can stack π-π bonds with the aromatic groups formed during the carbonization of chitosan, thereby improving the molecular order and thus affecting the microstructure of carbon materials and improving the uniformity of hybridization reaction.

[0027] (3) In this invention, potassium hydroxide is an activator. Potassium hydroxide can corrode carbon at the microscopic level, thereby activating it and generating a large number of complex structures. This facilitates the entry of gaseous products and small molecule products into these vacancies to form a large number of active sites, which is beneficial to the nitridation and hybridization process.

[0028] (4) In this invention, potassium silicate is used as an activating and strengthening agent. Potassium silicate with a low modulus (2.0-2.5) has high solubility and good compatibility with strong alkaline solutions. It has a high potassium oxide content, but also contains a certain amount of silicon dioxide. This allows it to both produce a glass transition effect in the high-temperature pyrolysis step to solidify and strengthen the microstructure and improve the macroscopic mechanical strength, and produce silicon dioxide as a hard template to prevent excessive activation and corrosion of carbon materials, which would lead to the collapse of the microstructure. It can also produce more K2O and potassium hydroxide as activating agents in the process.

[0029] The CS-derived carbon material electrode prepared by this invention can not only efficiently remove heavy metal ions from water by electrochemical deposition, but also has environmentally friendly components and low raw material costs, making it highly valuable for application and promotion. Attached Figure Description

[0030] Figure 1 This is a diagram showing the removal effect of Example 1.

[0031] Figure 2 This is a diagram showing the removal effect of Example 2.

[0032] Figure 3 This is the CV test diagram of Example 3.

[0033] Figure 4 This is the CV test diagram of Example 4.

[0034] Figure 5 This is the EIS Nyquist plot of Example 5.

[0035] Figure 6 These are the removal effect diagrams for comparison examples 1 to 4. Detailed Implementation

[0036] The present invention will be further described below with reference to embodiments, but the scope of protection of the present invention is not limited thereto.

[0037] Example 1

[0038] (1) Pre-treatment of carbon fiber felt

[0039] Specifically, carbon fiber felt is immersed in a nitric acid-hydrochloric acid mixture with a mass ratio of nitric acid, hydrochloric acid, and water of 1:2:10, heated to 50°C, then removed and thoroughly rinsed with deionized water until the rinsing solution is neutral. After rinsing, it is dried at 50°C for 3 hours to obtain the modified carbon felt carrier.

[0040] (2) Prepare and load CS-arginine-IAA precursor solution onto modified carbon felt carrier.

[0041] Specifically, CS, arginine, IAA, glacial acetic acid, and deionized water are mixed in a mass ratio of 2:1:0.5:2:100 to prepare a CS-arginine-IAA precursor solution. The modified carbon felt prepared in step (1) is then immersed in the CS-arginine-IAA precursor solution and stirred thoroughly to allow it to become wetted.

[0042] (3) Low-temperature hydrothermal carbonization

[0043] Specifically, the CS-arginine-IAA precursor solution prepared in step (2) above was placed together with carbon fiber felt in a hydrothermal reactor and hydrothermally carbonized at 240°C for 12 hours to obtain a CS hydrothermal carbonized electrode, which was then dried at 70°C for 2 hours.

[0044] (4) Prepare and load activator onto hydrothermal carbonized carbon felt

[0045] Specifically, potassium hydroxide, potassium silicate, and deionized water are thoroughly mixed in a mass ratio of 1.5:0.6:100 to prepare an activation and strengthening solution; the CS hydrothermal carbonized electrode that has been dried in step (3) above is immersed in the activation and strengthening solution and thoroughly stirred to wet it; the CS hydrothermal carbonized felt containing the activation and strengthening solution is taken out and then dried at 60°C for 4 hours to obtain a CS hydrothermal carbonized electrode containing the activation and strengthening agent.

[0046] (5) High-temperature pyrolysis activation

[0047] The hydrothermal carbonization electrode containing the activating and reinforcing agent CS prepared in step (4) above was placed in a tube furnace with nitrogen as the protective gas; the temperature was increased at a rate of 3℃ / min, held at a high temperature of 1000℃ for 1h, and then cooled to the ambient temperature at a rate of 5℃ / min before being taken out to obtain the CS high-temperature pyrolysis electrode.

[0048] (6) Post-processing

[0049] The CS high-temperature pyrolysis electrode prepared in step (5) was immersed in dilute hydrochloric acid with a concentration of 0.05 mol / L for 6 h; it was then washed with deionized water until the washing solution was neutral, and then dried at 50 °C for 3 h to finally obtain the CS-derived carbon electrode.

[0050] (7) Electrochemical deposition removal test of heavy metal ions

[0051] Specifically, the CS-derived carbon electrode is the working electrode, the platinum-plated titanium mesh is the counter electrode, and the saturated calomel electrode is the reference electrode. All of these electrodes are connected to an electrochemical workstation.

[0052] When using the CS-derived carbon electrode for electrochemical deposition to remove heavy metal ions, a pulse potential of -6 to -1V (relative to the reference electrode) is applied to the electrode, with a duty cycle of 75% and a frequency of 100Hz.

[0053] The removal experiment was conducted using simulated wastewater, with Cu ions in the simulated wastewater. 2+ The concentration of CuSO4 was 300 ppm; the remaining components were Na2SO4 with a concentration of 400 ppm.

[0054] Experimental results show that Cu at 1.5h 2+ The removal rate reached 81.02%, and Cu was removed after 3 hours. 2+ The removal rate reached 91.33%; after the experiment, copper-red deposits were observed on the electrode sheet.

[0055] The removal experiment was conducted using simulated wastewater, with the simulated wastewater containing Pb ions. 2+ The concentration was 200 ppm, which was Pb(NO3)2; the remaining components were NaNO3, with a concentration of 400 ppm.

[0056] Experimental results show that Pb at 1.5h 2+ The removal rate reached 71.78%, and Pb was removed after 3 hours. 2+ The removal rate reached 91.26%; after the experiment, grayish-white deposits were observed on the electrode sheet.

[0057] Example 2

[0058] (1) Pre-treatment of carbon fiber felt

[0059] Specifically, carbon fiber felt is immersed in a nitric acid-hydrochloric acid mixture with a mass ratio of nitric acid, hydrochloric acid, and water of 1:4:10, heated to 70°C, then removed and thoroughly rinsed with deionized water until the rinsing solution is neutral. After rinsing, it is dried at 60°C for 2 hours to obtain the modified carbon felt carrier.

[0060] (2) Prepare and load CS-arginine-IAA precursor solution onto modified carbon felt.

[0061] Specifically, CS, arginine, IAA, glacial acetic acid, and deionized water are mixed in a mass ratio of 4:1.5:1:2:100 and stirred thoroughly to prepare a CS-arginine-IAA precursor solution. The modified carbon felt prepared in step (1) above is immersed in the CS-arginine-IAA precursor solution and stirred thoroughly to allow it to be soaked.

[0062] (3) Low-temperature hydrothermal carbonization

[0063] Specifically, the CS-arginine-IAA precursor solution prepared in step (2) above was placed together with carbon fiber felt in a hydrothermal reactor and hydrothermally carbonized at 200°C for 10 hours to obtain a CS hydrothermal carbonized electrode, which was then dried at 75°C for 2 hours.

[0064] (4) Prepare and load activator onto hydrothermal carbonized carbon felt

[0065] Specifically, potassium hydroxide, potassium silicate, and deionized water are thoroughly mixed in a mass ratio of 2:1:100 to prepare an activation and strengthening solution; the CS hydrothermal carbonization electrode that has been dried in step (3) above is immersed in the activation and strengthening solution and thoroughly stirred to wet it; the CS hydrothermal carbonization felt containing the activation and strengthening solution is taken out and then dried at 60°C for 4 hours to obtain a CS hydrothermal carbonization electrode containing the activation and strengthening agent.

[0066] (5) High-temperature pyrolysis activation

[0067] The hydrothermal carbonization electrode containing the activating and reinforcing agent CS prepared in step (4) above was placed in a tube furnace with an inert gas as the protective gas; the temperature was increased at a rate of 5℃ / min, held at a high temperature of 900℃ for 1h, and then cooled to the ambient temperature at a rate of 3℃ / min before being taken out to obtain the CS high-temperature pyrolysis electrode.

[0068] (6) Post-processing

[0069] The CS high-temperature pyrolysis electrode prepared in step (5) was immersed in dilute hydrochloric acid with a concentration of 0.1 mol / L for 4 h; it was then washed with deionized water until the washing solution was neutral, and then dried at 80 °C for 2 h to finally obtain the CS-derived carbon electrode.

[0070] (7) Electrochemical deposition removal test of heavy metal ions

[0071] Specifically, the CS-derived carbon electrode is the working electrode, the platinum-plated titanium mesh is the counter electrode, and the saturated calomel electrode is the reference electrode. All of these electrodes are connected to an electrochemical workstation.

[0072] When using the CS-derived carbon electrode for electrochemical deposition to remove heavy metal ions, a pulse potential of -6 to -1V (relative to the reference electrode) is applied to the electrode, with a duty cycle of 75% and a frequency of 100Hz.

[0073] The removal experiment was conducted using simulated wastewater, with Cu ions in the simulated wastewater. 2+ The concentration of CuSO4 was 300 ppm; the remaining components were Na2SO4 with a concentration of 400 ppm.

[0074] Experimental results show that Cu at 1.5h 2+ The removal rate reached 69.26%, and Cu was removed after 3 hours. 2+ The removal rate reached 93.02%; after the experiment, copper-red deposits were observed on the electrode sheet.

[0075] The removal experiment was conducted using simulated wastewater, with the simulated wastewater containing Pb ions. 2+ The concentration was 200 ppm, which was Pb(NO3)2; the remaining components were NaNO3, with a concentration of 400 ppm.

[0076] Experimental results show that Pb at 1.5h 2+ The removal rate reached 73.71%, and Pb was removed after 3 hours. 2+ The removal rate reached 92.73%; after the experiment, grayish-white deposits were observed on the electrode sheet.

[0077] Example 3

[0078] (1) Preparation of CS-derived carbon electrode

[0079] The electrode preparation method in Example 3 of this invention is the same as steps (1) to (6) in Example 1.

[0080] (2)Cu 2+ CV testing of ions

[0081] Specifically, the CS-derived carbon electrode is the working electrode, the platinum-plated titanium mesh is the counter electrode, and the saturated calomel electrode is the reference electrode. All of these electrodes are connected to an electrochemical workstation.

[0082] When using the CS-derived carbon electrode to test CV, a potential range of -1 to 1V (relative to the reference electrode) is applied to the electrode, and the scan rate is 5mV.

[0083] CV tests were conducted using simulated wastewater, with Cu being the heavy metal ion in the simulated wastewater. 2+ The concentration of CuSO4 was 300 ppm; the remaining components were Na2SO4 with a concentration of 400 ppm.

[0084] Experimental results show that obvious redox peaks appeared, and the redox peak potentials are consistent with Cu2+ The redox potential of Cu confirms that 2+ Electrochemical reduction deposition occurred on the electrode surface.

[0085] Example 4

[0086] (1) Preparation of CS-derived carbon electrode

[0087] The electrode preparation method in Example 4 of this invention is the same as steps (1) to (6) in Example 2.

[0088] (3)Pb 2+ CV testing of ions

[0089] Specifically, the CS-derived carbon electrode is the working electrode, the platinum-plated titanium mesh is the counter electrode, and the saturated calomel electrode is the reference electrode. All of these electrodes are connected to an electrochemical workstation.

[0090] When using the CS-derived carbon electrode to test CV, a potential range of -1.5 to 1.5 V (relative to the reference electrode) is applied to the electrode, and the scan rate is 5 mV.

[0091] CV tests were conducted using simulated wastewater, with the simulated wastewater containing Pb as the heavy metal ion. 2+ The concentration was 200 ppm, which was Pb(NO3)2; the remaining components were NaNO3, with a concentration of 400 ppm.

[0092] Experimental results show that a distinct redox peak appeared, and the redox peak potentials are consistent with those of Pb. 2+ The redox potential of Pb confirmed that 2+ Electrochemical reduction deposition occurred on the electrode surface.

[0093] Example 5

[0094] (1) Preparation of CS-derived carbon electrode

[0095] The electrode preparation method in Example 3 of this invention is the same as steps (1) to (6) in Example 1.

[0096] (2) EIS test of electrodes

[0097] Specifically, the CS-derived carbon electrode is the working electrode, the platinum-plated titanium mesh is the counter electrode, and the saturated calomel electrode is the reference electrode. All of these electrodes are connected to an electrochemical workstation.

[0098] EIS tests were performed in a mixed solution of CuSO4 and Na2SO4, with CuSO4 concentration of 300 ppm and Na2SO4 concentration of 400 ppm.

[0099] Experimental results show that when the experimental data are fitted with a Nyquist plot, the curves in the plot are semicircular-sloping. As can be seen from the plot, the smaller Rs value indicates that the solution resistance is small, which is conducive to ion transfer and charge migration. The smaller Rct value can be seen from the radius of the circle, which indicates that the electrode surface has high electrochemical activity and low charge transfer resistance, which is conducive to the reaction.

[0100] Comparative Example 1

[0101] (1) Preparation of CS hydrothermal carbonized carbon felt

[0102] Specifically, the steps are the same as in Example 1, but in step 2, the mass ratio of CS, arginine, IAA, glacial acetic acid, and deionized water is changed to 0.1:1:0.5:2:100.

[0103] (2) Electrochemical deposition removal test of heavy metal ions

[0104] Specifically, the CS hydrothermal carbonized felt prepared above is used as the working electrode, the platinum-plated titanium mesh is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode, and the electrodes are connected to an electrochemical workstation.

[0105] When using the CS hydrothermal carbonized carbon felt electrochemical deposition to remove heavy metal ions, a pulse potential (relative to the reference electrode) of -1 to -6V is applied to the electrode, with a duty cycle of 75% and a frequency of 100Hz.

[0106] The removal experiment was conducted using simulated wastewater, with Cu ions in the simulated wastewater. 2+ The concentration of CuSO4 was 150 ppm; the remaining components were Na2SO4 with a concentration of 400 ppm.

[0107] Experimental results show that Cu at 1.5h 2+ When the removal rate is less than 25%, Cu is removed after 3 hours. 2+ The removal rate was only 40.3%.

[0108] The comparative results show that, compared with Example 1, reducing the concentration of carbon and nitrogen sources to a lower level results in less active material forming on the modified carbon felt support, which is beneficial to Cu. 2+ The removal rate was significantly lower than that in Example 1.

[0109] Comparative Example 2

[0110] (1) Preparation of CS-derived carbon electrode

[0111] Specifically, the steps are the same as in Example 2, but in step 4, the mass ratio of potassium hydroxide, potassium silicate, and deionized water is changed to 0.1:1:100.

[0112] (2) Electrochemical deposition removal test of heavy metal ions

[0113] Specifically, the CS-derived carbon electrode prepared above is used as the working electrode, the platinum-plated titanium mesh is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode, and each electrode is connected to an electrochemical workstation.

[0114] When using the CS-derived carbon electrode for electrochemical deposition to remove heavy metal ions, a pulse potential of -1 to -6V (relative to the reference electrode) is applied to the electrode, with a duty cycle of 75% and a frequency of 100Hz.

[0115] The removal experiment was conducted using simulated wastewater, with the simulated wastewater containing Pb ions. 2+ The concentration was 100 ppm, which was Pb(NO3)2; the remaining components were NaNO3, with a concentration of 400 ppm.

[0116] Experimental results show that Pb at 1.5h 2+ Removal rate 46.37%, Pb at 3h 2+ The removal rate was only 67.50%.

[0117] The comparative results show that, compared with Example 2, reducing the concentration of the activator potassium hydroxide to a low level results in insufficient activation of the carbon material during the high-temperature pyrolysis step, which affects the Pb content. 2+ The removal rate was significantly lower than that in Example 2.

[0118] Comparative Example 3

[0119] (1) Preparation of CS-derived carbon electrode

[0120] Specifically, the steps and conditions are the same as in Example 1, but the mass ratio of CS, arginine, IAA, glacial acetic acid, and deionized water in step 2 is changed to 2:1:0.01:2:100.

[0121] (2) Electrochemical deposition removal test of heavy metal ions

[0122] Specifically, the CS-derived carbon electrode prepared above is used as the working electrode, the platinum-plated titanium mesh is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode, and each electrode is connected to an electrochemical workstation.

[0123] When using the CS-derived carbon electrode for electrochemical deposition to remove heavy metal ions, a pulse potential of -1 to -6V (relative to the reference electrode) is applied to the electrode, with a duty cycle of 75% and a frequency of 100Hz.

[0124] The removal experiment was conducted using simulated wastewater, with Cu ions in the simulated wastewater. 2+ The concentration of CuSO4 was 150 ppm; the remaining components were Na2SO4 with a concentration of 400 ppm.

[0125] Experimental results show that Cu at 1.5h2+ The removal rate did not reach 50%, and Cu was removed after 3 hours. 2+ The removal rate was only 71.94%.

[0126] The comparative results show that, compared with Example 1, reducing the concentration of the hybridization enhancer IAA to a low level results in uneven hybridization reactions of carbon materials during low-temperature hydrothermal and high-temperature pyrolysis, which has a negative impact on Cu. 2+ The removal rate decreased compared to Example 1.

[0127] Comparative Example 4

[0128] (1) Preparation of CS-derived carbon electrode

[0129] Specifically, the steps and conditions are the same as in Example 1, but in step 4, the mass ratio of potassium hydroxide, potassium silicate, and deionized water is changed to 2:0.01:100.

[0130] (2) Electrochemical deposition removal test of heavy metal ions

[0131] Specifically, the CS-derived carbon electrode prepared above is used as the working electrode, the platinum-plated titanium mesh is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode, and each electrode is connected to an electrochemical workstation.

[0132] When removing heavy metal ions using the CS hydrothermal carbonized carbon felt electrochemical deposition, a pulse potential of -1 to -6V (relative to the reference electrode) is applied to the electrode, with a duty cycle of 75% and a frequency of 100Hz.

[0133] The removal experiment was conducted using simulated wastewater, with the simulated wastewater containing Pb ions. 2+ The concentration was 100 ppm, which was Pb(NO3)2; the remaining components were NaNO3, with a concentration of 400 ppm.

[0134] Experimental results show that fragments fell from the electrode surface during the cleaning and experimental processes; at 1.5 h, Pb 2+ Removal rate 54.69%, Pb at 3h 2+ The removal rate was only 78.86%.

[0135] The comparative results show that, compared with Example 2, reducing the concentration of the activating and strengthening agent potassium silicate to a low level resulted in fragments falling off the electrode surface during the cleaning and experimental processes. This indicates that the strength of the carbon material has decreased, and the microporous structure may have collapsed due to over-activation, reducing the number of active sites and affecting Pb. 2+ The removal rate was lower than that in Example 2.

Claims

1. A method for preparing a chitosan-derived carbon electrode, characterized in that, The steps are as follows: (1) Pretreatment of carbon fiber felt: The carbon fiber felt is immersed in a mixture of nitric acid and hydrochloric acid and heated, then taken out, washed with deionized water, and dried to obtain modified carbon felt carrier. (2) Preparation of chitosan, arginine, and indole-3-acetic acid (IAA) precursor solution: Chitosan, arginine, IAA, and glacial acetic acid are dissolved in deionized water and stirred to obtain chitosan-arginine-IAA precursor solution; In step (2), the mass ratio of chitosan, arginine, IAA, glacial acetic acid, and deionized water in the chitosan-arginine-IAA precursor solution is (2~4):(1~2):(0.5~1):2:100; (3) Low-temperature hydrothermal carbonization: The modified carbon felt carrier is immersed in the chitosan-arginine-IAA precursor solution prepared in step (2) and subjected to hydrothermal carbonization reaction. After hydrothermal carbonization, it is taken out and dried to obtain the chitosan hydrothermal carbonized electrode. (4) Preparation of a chitosan hydrothermal carbonized electrode containing an activating and reinforcing agent: Dissolve potassium hydroxide and potassium silicate in deionized water to prepare an activating and reinforcing solution; immerse the chitosan hydrothermal carbonized electrode in the activating and reinforcing solution and stir to wet it; take out the chitosan hydrothermal carbonized electrode containing the activating and reinforcing solution and dry it to obtain a chitosan hydrothermal carbonized electrode containing an activating and reinforcing agent; In step (4), the activating and reinforcing solution is composed of potassium hydroxide, potassium silicate and deionized water in a mass ratio of (1~2):(0.5~1):100; the drying temperature is 50~80℃ and the time is 2~4h; (5) High-temperature pyrolysis activation: The chitosan hydrothermal carbonization electrode containing the activation enhancer prepared in step (4) is placed in a tube furnace, and pyrolyzed at high temperature with inert gas as the protective gas. After cooling, it is taken out to obtain the chitosan high-temperature pyrolysis electrode. (6) Post-processing: The chitosan high-temperature pyrolysis electrode prepared in step (5) is immersed in dilute hydrochloric acid, washed with deionized water, and dried in an oven to finally obtain the chitosan-derived carbon electrode.

2. The method for preparing the chitosan-derived carbon electrode according to claim 1, characterized in that: In step (1), the mass ratio of nitric acid, hydrochloric acid and water in the nitric acid-hydrochloric acid mixed acid is 1:(1~4):10, the heating temperature is 50~70℃, the drying temperature is 50~80℃, and the time is 2~4h.

3. The method for preparing the chitosan-derived carbon electrode according to claim 1, characterized in that: In step (3), the hydrothermal carbonization temperature is 200~240℃ and the time is 10~12h; the drying temperature is 50~80℃ and the time is 2~4h.

4. The method for preparing the chitosan-derived carbon electrode according to claim 1, characterized in that: In step (5), the inert gas is nitrogen, and the temperature is increased by programmed heating at a rate of 3-5℃ / min; the high-temperature pyrolysis temperature is 900-1000℃, and the holding time is 0.5-1h; the cooling rate is 3-5℃ / min.

5. The method for preparing the chitosan-derived carbon electrode according to claim 1, characterized in that: In step (6), the concentration of dilute hydrochloric acid is 0.05~0.1mol / L, the soaking time is 4~6h, the drying temperature is 50~80℃, and the time is 2~4h.

6. A chitosan-derived carbon electrode, characterized in that, It is prepared by the method described in any one of claims 1 to 5.

7. The application of the chitosan-derived carbon electrode prepared by the method of claim 1 in the electrochemical deposition method for removing heavy metal ions from water.

Citation Information

Patent Citations

  • Atomic-scale dispersed bimetal site anchored nitrogen-doped carbon material as well as preparation and application thereof

    CN112647095A

  • Product for relieving crop phytotoxicity and rapidly recovering growth and preparation and use methods thereof

    CN113080191A